RANGKAIAN PENGATUR ALIRAN CAIRAN INFUS BERBASIS ATMEGA 8535 - Amanda Amelia; Kiki Prawiroredjo (Website, 2017)
Automatic Infusion Fluid Flow Regulator circuit Based on ATMEGA 8535 is a tool that changes the flow of infusion fluid from the first tube to the second tube when the fluid in the first tube has been exhausted. This tool equips with a regulator to control the number of droplets per minute from infusion fluids. The circuit consist of Light Emitting Diode (LED), infrared photodiode sensors, push buttons, two seven segments, two DC motors, and a microcontroller ATMEGA 8535 . The microcontroller processes the number of droplets and displays on seven segments, adjusts the position of the motor that drives the clamp of rubber tube from the infusion tube and detects the level of infusion fluid in the tube to close or open the flow of the fluid. After the tool is assembled and tested, the circuit has been run according to the design. Two seven segments display the number from 10 to 20 drops per minute. Sensor detects the presence or absence of liquid in the tube. DC motor clamps the rubber tube from the infusion tube in accordance with the required droplets and change the flow of rubber tube from the first infusion tube to the second infusion tube if the fluid from the first tube has run out. Rangkaian Pengatur Aliran Cairan Infus Otomatis Berbasis ATMEGA 8535 adalah sebuah alat yang dapat mengganti aliran cairan infus dari tabung pertama ke tabung kedua apabila cairan pada tabung infus pertama telah habis. Alat ini dilengkapi dengan pengatur jumlah tetesan cairan infus per menit. Komponen pembentuk rangkaian terdiri dari sensor photodioa infrared, tombol tekan, seven segment, motor DC, dan mikrokontroller ATMEGA 8535. Mikrokontroler berfungsi sebagai pemproses jumlah tetesan yang ingin ditampilkan pada seven segment, mengatur posisi motor yang menggerakkan klem infus dan mendeteksi tinggi cairan pada tabung tetes untuk menutup atau membuka selang infus. Sesudah alat ini dirangkai dan diuji, rangkaian telah berjalan sesuai dengan rancangan yang dibuat. Dua seven segment menampilkan jumlah tetesan infus yaitu dari 10 sampai 20 tetes per menit. Sensor dapat mendeteksi ada tidaknya cairan pada tabung tetes. Motor DC menjepit sesuai dengan tetesan yang dibutuhkan dan dapat mengganti aliran cairan infus dari tabung pertama ke tabung ke dua bila cairan pada tabung pertama telah habis.